Quantitative determination of canagliflozin in human plasma samples using a validated HPTLC method and its application to a pharmacokinetic study in rats. (10th July 2020) - Alam, Prawez; Iqbal, Muzaffar; Foudah, Ahmed I.; Alqarni, Mohammad H.; Shakeel, Faiyaz
Abstract: Canagliflozin (CNZ) is the first sodium–glucose co‐transporter‐2 inhibitor approved for treatment of type 2 diabetes mellitus. In the proposed work, a sensitive, rapid and validated high‐performance thin‐layer chromatography (HPTLC) method was established for the estimation of CNZ in human plasma for the first time. HPTLC analysis of CNZ and internal standard (sildenafil) was performed on glass coated silica gel 60 F254 HPTLC plates using a binary mixture of chloroform–methanol 9:1 (%, v/v) as the mobile phase. Densitometric detection was done at 295 nm. Retardation factor values were obtained as 0.22 and 0.52 for the CNZ and the IS, respectively. The linearity range of CNZ was obtained as 200–3, 200 ng/ml. A simple protein precipitation method was used for the extraction of analyte from plasma using methanol. The proposed HPTLC technique was validated for linearity, accuracy, precision and robustness. The proposed HPTLC technique was successfully utilized for the assessment of pharmacokinetic profile of CNZ in rats after oral administration. After oral administration, the peak plasma concentration of CNZ was obtained as 1458.01 ng/ml in 2 h. The proposed HPTLC method could be applied to the study of the pharmacokinetic profile of pharmaceutical formulations containing CNZ.